The psychology of strength and conditioning - Tod, David; Lavallee, David 1969- (London New York Routledge, 2012)
"An effective strength and conditioning program underpins the training regime of every successful athlete or sportsperson and it is now widely recognised that psychology plays a significant role in the application of strength and conditioning principles. This is the first book to examine the importance of psychological factors in strength and conditioning and to offer a comprehensive overview of current research, theory and best practice. Written by a team of leading international researchers and practitioners, the book looks at how psychology influences training and performance and how training can influence an individual's psychological well-being. It explores a range of key topics in contemporary sport psychology and athletic training, including: mental skills training behaviour change psychology in professional practice psychological problems, including exercise dependence, eating disorders and steroid use Throughout, the book combines evidence-based research with discussion of the practical issues facing athletes, coaches and sport science professionals. By firstly developing our understanding of the latest psychological skills and techniques used by athletes and coaches to maximise strength and conditioning training and performance, and then the ways other psychological factors influence, and are influenced by, strength and conditioning training, this book represents invaluable reading for all advanced students, researchers, trainers and sport scientists with an interest in strength and conditioning or sport psychology"--
1. mental skills training and strength and conditioning/ Stephen D. Mellalieu and David Shearer -- 2. Social psychological theories and models/ Sarah McLachlan, Derwin King-Chung, Dave Keatley and martin Hagger -- 3. Perceptual monitoring in strength and power/ Michael McGuigan -- 4. Exercise, self-esteem and self-perceptions/ Magnus Lindwall -- 5. Resistance training and mental health/ Shawn M. Arent and Devon L. Golem -- 6. Exercise dependence/ Dave Smith and Bruce D. Hale -- 7. Drive for muscularity/ Christian Edwards, David Tod. Todd G. Morrison and Gyozo Molnar -- 8. Eating disorder in sport/ Justine J. Reel and Nick Galli -- 9. The misuse of anabolic-androgenic steroids/ Susan H. Backhouse -- 10. Professional development in strength and conditioning coaches/ David Tod and David Lavallee
Keywords: Muscle strength; Physical education and training -- Psychological aspects; Physical fitness -- Psychological aspects; Sports -- Psychological aspects